Diffusion and surface alloying of gradient nanostructured metals - Wang, Zhenbo; Lu, Ke (Beilstein Journal of Nanotechnology, 2017)
Gradient nanostructures (GNSs) have been optimized in recent years for desired performance. The diffusion behavior in GNS metals is crucial for understanding the diffusion mechanism and relative characteristics of different interfaces that provide fundamental understanding for advancing the traditional surface alloying processes. In this paper, atomic diffusion, reactive diffusion, and surface alloying processes are reviewed for various metals with a preformed GNS surface layer. We emphasize the promoted atomic diffusion and reactive diffusion in the GNS surface layer that are related to a higher interfacial energy state with respect to those in relaxed coarse-grained samples. Accordingly, different surface alloying processes, such as nitriding and chromizing, have been modified significantly, and some diffusion-related properties have been enhanced. Finally, the perspectives on current research in this field are discussed.
Keywords: diffusion; gradient nanostructures; grain boundary; interface; surface alloying

(untitled) - Fang, T. H.; Li, W. L.; Tao, N. R.; Lu, K. (Science, 2011)

(untitled) - Wu, X.; Jiang, P.; Chen, L.; Yuan, F.; Zhu, Y. T. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Wei, Y.; Li, Y.; Zhu, L.; Liu, Y.; Lei, X.; Wang, G.; Wu, Y.; Mi, Z.; Liu, J.; Wang, H.; Gao, H. (Nat. Commun., 2014)

(untitled) - Han, Z.; Zhang, Y.; Lu, K. (J. Mater. Sci. Technol., 2008)

(untitled) - Wang, Z. B.; Tao, N. R.; Li, S.; Wang, W.; Liu, G.; Lu, J.; Lu, K. (Mater. Sci. Eng., A, 2003)

(untitled) - Yang, L.; Tao, N. R.; Lu, K.; Lu, L. (Scr. Mater., 2013)

(untitled) - Huang, H. W.; Wang, Z. B.; Lu, J.; Lu, K. (Acta Mater., 2015)

(untitled) - Harrison, L. G. (Trans. Faraday Soc., 1961)

(untitled) - Lu, K.; Lu, J. (J. Mater. Sci. Technol., 1999)

(untitled) - Lu, K.; Lu, J. (Mater. Sci. Eng., A, 2004)

(untitled) - Lu, K. (Nat. Rev. Mater., 2016)

Proceedings of the 2nd Riso International Symposium on Metallurgy and Materials Science - Gleiter, H. (Materials with Ultrafine Grain Size, Roskilde, Denmark, 1981)

(untitled) - Gleiter, H. (Prog. Mater. Sci., 1989)

(untitled) - Horváth, J.; Birringer, R.; Gleiter, H. (Solid State Commun., 1987)

(untitled) - Schumacher, S.; Birringer, R.; Strauss, R.; Gleiter, H. (Acta Metall., 1989)

(untitled) - Höfler, H. J.; Averback, R. S.; Hahn, H.; Gleiter, H. (J. Appl. Phys., 1993)

(untitled) - Divinski, S. V.; Hisker, F.; Kang, Y.-S.; Lee, J.-S.; Herzig, C. (Acta Mater., 2004)

(untitled) - Würschum, R.; Farber, P.; Dittmar, R.; Scharwaechter, P.; Frank, W.; Schaefer, H.-E. (Phys. Rev. Lett., 1997)

(untitled) - Würschum, R.; Reimann, K.; Gruss, S.; Kubler, A.; Scharwaechter, P.; Frank, W.; Kruse, O.; Carstanjen, H. D.; Schaefer, H. E. (Philos. Mag. B, 1997)

(untitled) - Kolobov, Yu. R.; Grabovetskaya, G. P.; Ivanov, M. B.; Zhilyaev, A. P.; Valiev, R. Z. (Scr. Mater., 2001)

(untitled) - Amouyal, Y.; Divinski, S. V.; Estrin, Y.; Rabkin, E. (Acta Mater., 2007)

(untitled) - Nazarov, A. A.; Romanov, A. E.; Valiev, R. Z. (Scr. Mater., 1996)

(untitled) - Valiev, R. Z.; Islamgaliev, R. K.; Alexandrov, I. V. (Prog. Mater. Sci., 2000)

(untitled) - Wilde, G.; Ribbe, J.; Reglitz, G.; Wegner, M.; Rösner, H.; Estrin, Y.; Zehetbauer, M.; Setman, D.; Divinski, S. (Adv. Eng. Mater., 2010)

(untitled) - Straumal, B. B.; Kogtenkova, O. A.; Muktepavela, F.; Kolesnikova, K. I.; Bulatov, M. F.; Straumal, P. B.; Baretzky, B. (Mater. Lett., 2015)

(untitled) - Ribbe, J.; Baither, D.; Schmitz, G.; Divinski, S. V. (Phys. Rev. Lett., 2009)

(untitled) - Divinski, S. V.; Ribbe, J.; Baither, D.; Schmitz, G.; Reglitz, G.; Rösner, H.; Sato, K.; Estrin, Y.; Wilde, G. (Acta Mater., 2009)

(untitled) - Klinger, L.; Rabkin, E. (Acta Mater., 1999)

(untitled) - Tao, N. R.; Wang, Z. B.; Tong, W. P.; Sui, M. L.; Lu, J.; Lu, K. (Acta Mater., 2002)

(untitled) - Wang, K.; Tao, N. R.; Liu, G.; Lu, J.; Lu, K. (Acta Mater., 2006)

(untitled) - Wang, Z. B.; Tao, N. R.; Tong, W. P.; Lu, J.; Lu, K. (Acta Mater., 2003)

(untitled) - Wang, Z. B.; Lu, J.; Lu, K. (Acta Mater., 2005)

(untitled) - Lu, S. D.; Wang, Z. B.; Lu, K. (Mater. Sci. Eng., A, 2010)

(untitled) - Srikrishnan, V.; Ficalora, P. J. (Metall. Trans. A, 1975)

Handbook of Grain and Interphase Boundary Diffusion Data - Kaur, I.; Gust, W.; Kozma, L. (Ziegler Press, 1989)

Materials Science and Engineering: An Introduction - Callister, W. D. (John Wiley & Sons, 2000)

(untitled) - Suryanarayana, C. (Int. Mater. Rev., 1995)

(untitled) - Wang, Z. B.; Lu, K.; Wilde, G.; Divinski, S. V. (Acta Mater., 2010)

(untitled) - Amouyal, Y.; Divinski, S. V.; Klinger, L.; Rabkin, E. (Acta Mater., 2008)

(untitled) - Divinski, S. V.; Reglitz, G.; Rösner, H.; Estrin, Y.; Wilde, G. (Acta Mater., 2011)

(untitled) - Dickenscheid, W.; Birringer, R.; Gleiter, H.; Kanert, O.; Michel, B.; Günther, B. (Solid State Commun., 1991)

(untitled) - Wang, H. L.; Wang, Z. B.; Lu, K. (Acta Mater., 2011)

Fundamentals of Grain and Interphase Boundary Diffusion - Kaur, I.; Mishin, Y.; Gust, W. (John Wiley & Sons, 1995)

(untitled) - Mishin, Y. M. (Defect Diffus. Forum, 2001)

(untitled) - Wang, Z. B.; Tao, N. R.; Tong, W. P.; Lu, J.; Lu, K. (Defect Diffus. Forum, 2006)

(untitled) - Straumal, B. B.; Mazilkin, A. A.; Baretzky, B. (Curr. Opin. Solid State Mater. Sci., 2016)

(untitled) - Straumal, B. B.; Sauvage, X.; Baretzky, B.; Mazilkin, A. A.; Valiev, R. Z. (Scr. Mater., 2014)

(untitled) - Divinski, S.; Lohmann, M.; Herzig, C.; Straumal, B.; Baretzky, B.; Gust, W. (Phys. Rev. B, 2005)

(untitled) - Straumal, B. B.; Noskovich, O. I.; Semenov, V. N.; Shvindlerman, L. S.; Gust, W.; Predel, B. (Acta Metall. Mater., 1992)

(untitled) - Cantwell, P. R.; Tang, M.; Dillon, S. J.; Luo, J.; Rohrer, G. S.; Harmer, M. P. (Acta Mater., 2014)

(untitled) - Wang, Z. B.; Lu, K.; Wilde, G.; Divinski, S. V. (Scr. Mater., 2011)

(untitled) - Wang, Z. B.; Lu, K.; Wilde, G.; Divinski, S. (Appl. Phys. Lett., 2008)

(untitled) - Minkwitz, C.; Herzig, C.; Rabkin, E.; Gust, W. (Acta Mater., 1999)

(untitled) - Monzen, R.; Sumi, Y.; Kitagawa, K.; Mori, T. (Acta Metall. Mater., 1990)

(untitled) - Borisov, V. T.; Golikov, V. M.; Scherbedinskiy, G. V. (Phys. Met. Metallogr., 1964)

(untitled) - Divinski, S.; Ribbe, J.; Schmitz, G.; Herzig, C. (Acta Mater., 2007)

Interfaces in Materials - Howe, J. M. (Wiley, 1997)

(untitled) - Kidson, G. V. (J. Nucl. Mater., 1961)

(untitled) - Charlot, F.; Gaffet, E.; Zeghmati, B.; Bernard, F.; Niepce, J. C. (Mater. Sci. Eng., A, 1999)

(untitled) - Wiecinski, P.; Garbacz, H.; Murakami, H.; Kurzydlowski, K. J. (Phys. Status Solidi C, 2010)

(untitled) - Wang, H. L.; Wang, Z. B.; Lu, K. (Acta Mater., 2012)

(untitled) - Tong, W. P.; Tao, N. R.; Wang, Z. B.; Lu, J.; Lu, K. (Science, 2003)

(untitled) - Tong, W. P.; Tao, N. R.; Wang, Z. B.; Zhang, H. W.; Lu, J.; Lu, K. (Scr. Mater., 2004)

Phase Transformation in Metals and Alloys - Porter, D.; Easterling, K. (Chapman & Hall, 1992)

(untitled) - Katona, G. L.; Vladymyrskyi, I. A.; Makogon, I. M.; Sidorenko, S. I.; Kristaly, F.; Daróczi, L.; Csik, A.; Liebig, A.; Beddies, G.; Albrecht, M.; Beke, D. L. (Appl. Phys. A, 2014)

(untitled) - Embury, J. D.; Deschamps, A.; Brechet, Y. (Scr. Mater., 2003)

Nanophase materials: synthesis-properties-applications - Fecht, H. J. (Nanophase materials by mechanical attrition: synthesis and characterization, 1994)

(untitled) - Reumont, G.; Perrot, P.; Fiorani, J. M.; Hertz, J. (J. Phase Equilib., 2000)

(untitled) - Lehrer, E. (Z. Elektrochem. Angew. Phys. Chem., 1930)

(untitled) - Tong, W. P.; Han, Z.; Wang, L. M.; Lu, J.; Lu, K. (Surf. Coat. Technol., 2008)

(untitled) - Yang, H. P.; Wu, X. C.; Min, Y. A.; Wu, T. R.; Gui, J. Z. (Surf. Coat. Technol., 2013)

(untitled) - Balusamy, T.; Sankara Narayanan, T. S. N.; Ravichandran, K. (Surf. Coat. Technol., 2012)

(untitled) - Balusamy, T.; Sankara Narayanan, T. S. N.; Ravichandran, K.; Park, I. S.; Lee, M. H. (Surf. Coat. Technol., 2013)

(untitled) - Balusamy, T.; Sankara Narayanan, T. S. N.; Ravichandran, K.; Park, I. S.; Lee, M. H. (Vacuum, 2013)

(untitled) - Yang, H.; Wu, X.; Yang, Z.; Pu, S.; Wang, H. (J. Alloys Compd., 2014)

(untitled) - Sun, H. Q.; Shi, Y. N.; Zhang, M.-X.; Lu, K. (Surf. Coat. Technol., 2008)

(untitled) - Xiang, Z. D.; Datta, P. K. (Scr. Mater., 2006)

(untitled) - Si, X.; Lu, B. N.; Wang, Z. B. (J. Mater. Sci. Technol., 2009)

(untitled) - Gu, J. F.; Bei, D. H.; Pan, J. S.; Lu, J.; Lu, K. (Mater. Lett., 2002)

(untitled) - Balusamy, T.; Sankara Narayanan, T. S. N.; Ravichandran, K.; Park, I. S.; Lee, M. H. (Mater. Charact., 2013)

(untitled) - Zhang, H. W.; Wang, L.; Hei, Z. K.; Liu, G.; Lu, J.; Lu, K. (Z. Metallkd., 2003)

(untitled) - Lin, Y.; Lu, J.; Wang, L.; Xu, T.; Xue, Q. (Acta Mater., 2006)

(untitled) - Farokhzadeh, K.; Qian, J.; Edrisy, A. (Mater. Sci. Eng., A, 2014)

(untitled) - Ge, L.; Tian, N.; Lu, Z.; You, C. (Appl. Surf. Sci., 2013)

(untitled) - Sun, J.; Tong, W. P.; Zuo, L.; Wang, Z. B. (Mater. Des., 2013)

(untitled) - Zhan, Z.; He, Y.; Wang, D.; Gao, W. (Intermetallics, 2006)

(untitled) - Zhan, Z.; He, Y.; Wang, D.; Gao, W. (Oxid. Met., 2007)

(untitled) - Straumal, B.; Korneva, A.; Zięba, P. (Arch. Civil Mech. Eng., 2014)

(untitled) - Straumal, B. B.; Pontikis, V.; Kilmametov, A. R.; Mazilkin, A. A.; Dobatkin, S. V.; Baretzky, B. (Acta Mater., 2017)

(untitled) - Guo, S.; Wang, Z. B.; Wang, L. M.; Lu, K. (Surf. Coat. Technol., 2014)

(untitled) - Guo, S.; Wang, Z. B.; Lu, K. (J. Mater. Sci. Technol., 2015)

(untitled) - Liang, Y. L.; Wang, Z. B.; Zhang, J.; Zhang, J. B.; Lu, K. (Appl. Surf. Sci., 2016)

(untitled) - Fu, T.; Zhou, Z. F.; Zhou, Y. M.; Zhu, X. D.; Zeng, Q. F.; Wang, C. P.; Li, K. Y.; Lu, J. (Surf. Coat. Technol., 2012)

(untitled) - Wen, M.; Gu, J.-F.; Liu, G.; Wang, Z.-B.; Lu, J. (Surf. Coat. Technol., 2007)

(untitled) - Wen, M.; Gu, J.-F.; Liu, G.; Wang, Z.-B.; Lu, J. (Appl. Surf. Sci., 2008)

(untitled) - Lu, Y. H.; Wang, Z. B.; Song, Y. Y.; Rong, L. J. (Corros. Sci., 2016)

(untitled) - Konstantinović, M. J.; Bonny, G. (Acta Mater., 2015)

(untitled) - Liu, X. C.; Zhang, H. W.; Lu, K. (Science, 2013)

(untitled) - Liu, X. C.; Zhang, H. W.; Lu, K. (Scr. Mater., 2015)